Public Service Innovation: Driving the Growth of the Tourism Industry in Indonesia - Syaiful Bachri; Lorensius Lonik (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The tourism industry in Indonesia has witnessed substantial growth in recent years, positioning the country as a prominent destination in Southeast Asia. However, alongside this growth, there has been a growing need for improved public services to cater to the increasing number of tourists. This research aims to investigate the impact of public service innovation on the growth and sustainability of the tourism industry in Indonesia. Through a comprehensive analysis of innovative approaches and best practices in public service delivery, this study identifies key strategies and policies that have successfully enhanced the overall tourist experience. The findings highlight the pivotal role of public service innovation in driving the tourism sector's expansion, improving visitor satisfaction, and fostering sustainable development in Indonesia's tourism landscape.